A new peculiar muensterellid coleoid (Cephalopoda) from the Kimmeridge Clay Formation of Dorset (England). Issue 3 (June 2019) - Fuchs, Dirk
Abstract: A concretion from the lower Tithonian Kimmeridge Clay Formation ( Pectinatus Zone) found by Steve Etches yielded a gladius of a coleoid cephalopod. It is peculiar in shape and has an unusual ornamentation of radiating ribs and tubercles. The new form is named Etchesia martilli n. gen. n. sp. and preliminarily placed within the octobrachian family Muensterellidae based on its limpet-like gladius. Through the presence of radiating ribs as well as the absence of a narrow anterior rachis E. martilli n. gen. n. sp. is similar to Pearceiteuthis buyi from the Oxford Clay Formation (Callovian). The new muensterellid is unique in having an enrolled patella apex, which is located close to the posterior gladius rim. E. martilli n. gen. n. sp. represents the first muensterellid coleoid from the Kimmeridge Clay Formation. A phylogenetic relationship of E. martilli n. gen. n. sp. (and Pearceiteuthis ) with cirrate and incirrate octopods is discussed, although further information on soft parts such as the muscular mantle is necessary.